Índice de desenvolvimento humano municipal e seus indicadores: o desenvolvimento da região do médio curso superior da bacia hidrográfica do rio Apodi-Mossoró-RN - Souza Júnior, Francisco Canindé de (Universidade Federal Rural do Semi-Árido, 2016)
The aim of this study was to investigate the evolution and behavior of the Human Development Index Municipal –HDIM- the municipalities that make up the average upper reaches of the river basin of the River Basin Apodi/Mossoró – RN in Brazil. To do so using simple tools of descriptive statistics and georeferrenciado analysis through thematic maps on socioeconomic data, especially, HDIM calculated in the 1991-2010 period. The main results showed that, the HDIM of the analysis region of the municipalities had a shy evolution in its middle, whereas in 2010 there are still municipalities in low and middle ranking. The HDIM Education, despite having the lowest rates, was the most evolved, 204.68% in 2010. Regarding the indicators income and longevity, the latter with the highest rates, they obtained a minor evolution.
Keywords: Indicadores socioeconômicos; Bacia hidrográfica médio curso superior; Desenvolvimento regional; Socioeconomic indicators; Hydrographic basin upper middle course; Regional development; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA